Taj Salmani and His Work "Tarikhnoma" - Kamola Shavkat qizi Kayumova (International Journal on Integrated Education, 2022)
This article is dedicated to "Tarikhnoma" by Tadj Salmani covering the history of Amir Temur and Timurid rule in the Uzbek state in 1404-1409. The article highlights the life and activity of Tadj Salmani, his work "Tarikhnoma", the content, style, and significance of the source, researches, copies and translations of the source.